DESIGN OF MICROSTRIP ANTENNA DIMENSIONS BASED ON THE MATLAB GRAPHICAL USER INTERFACE (GUI) - Annisa, Tiara; Yacoub, Redi Ratiandi; Kusumawardhani, Eka (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2024)
Matlab is a software that is capable of performing calculations and simulations as well as developing Graphical User Interface (GUI) based application. The development of GUI based application can be used to perform complex calculations, one of which is the calculation of microstrip antenna dimensions. Microstrip antenna is a type of antenna that consists of a thin conductor laid over a dielectric substrate. The purpose of this research and development is to describe the programming language process so as to produce an effective GUI to determine the dimensions of the microstrip antenna to be designed. By providing input values in the form of dielectric constant, dielectric height, frequency, and impedance, the GUI will process this input into output values in the form of patch dimensions, feedline dimensions, and ground plane dimensions. This GUI will be made stand-alone so the users do not need to open the Matlab application to use it. The GUI will present buttons that are easy for users to use where each button has been adjusted to its respective function. The calculation of microstrip antenna dimensions from the GUI will be tested by comparing the output value with output value from the previous journals. In addition, to test the usefulness of each button, the blackbox testing where the result obtained were that all buttons could work according to their respective functions without any problems or errors so that the GUI can be used for determining the dimensions of microstrip antennas. Then, to test the appearance of the GUI, survey of potential users was conducted to determine the level of user satisfaction with resulting GUI.